Antibacterial test of lime leaf extract Citrus aurantifolia using ethanol solvent against E. coli bacteria - Yuliandini Pangestika; Alif Rahman Habibi; Alya Rahmaditya Arfan; Riska Dwi Putri (Indonesian Journal of Health Science, 2026)
Pathogenic bacteria that often cause health problems include Escherichia coli. This bacterium is a Gram-negative bacterium naturally found in the human digestive tract, but some strains are pathogenic and can cause diseases such as diarrhea, urinary tract infections, and infections in the digestive tract. Antibiotic resistance encourages the need to search for alternative antibacterial sources that are safer and more effective. The use of natural materials, particularly medicinal plants, has become one of the widely developed solutions because they are relatively easy to obtain and have lower side effects. Therefore, this research is expected to potentially provide a drug candidate from natural materials. This study showed results of antibacterial activity with high effectiveness, namely at a 50% concentration of 19 mm, while 25% concentration was 17 mm and 12.5% showed 12 mm. It is known that a clear zone above 20 mm indicates that the inhibitory power is very strong. A zone of 16-20 mm indicates that the bacteria's inhibitory power shows that the bacteria are strong in inhibiting bacterial growth. Moderate inhibitory power in bacterial growth is indicated by a size of 11-15 mm, and if the diameter is below 10 mm, it indicates that the bacteria's inhibitory power is weak. In this study, the results showed very good outcomes, with strong inhibitory power, making it a potential alternative in handling diseases caused by E. coli. These results support the potential of the test material to be further developed as an antibacterial agent. To achieve better research results, it is expected that future researchers can conduct tests on other types of bacteria.